PENGARUH MASA PERIKATAN AUDIT, ROTASI AUDIT DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT - Paputungan, Rahmita Dwinesia; Kaluge, David (Universitas Muhammadiyah Malang)
The aim of this study is to examine empirically the affect of audit tenure, audit rotation and public accounting firm size towards audit quality. Audit quality is proxied by using a going concern opinion which is an auditor?s opinion that explain a going concern of their client?s entity in where they do the audit. This study use purposive sampling to determine samples from manufacturing firms listed in Indonesia Stock Exchange for the year 2010?2016, focus study from 2011-2016, with total observations 105 samples from 143 populations. Data analysis techniques that used is in the form of a logistic regression analysis. The result of this study shows that audit tenure and audit rotation has no significant affect towards audit quality meanwhile public accounting firm size significantly affect the audit quality with negative direction.